Eculizumab as fast-acting rescue therapy for pembrolizumab-induced impending crisis state of myasthenia gravis: a case report - Ying Huang; Futian Wu; Yihan Xiong; Kangling Huang; Xin Chang; Xiaofeng Chen; Xiali Chen; Qiwen Zhang; Liangyu Zou; Xuejun Fu; Huadong Zhang; Qianhui Xu (Therapeutic Advances in Neurological Disorders)
Immune checkpoint inhibitors, such as pembrolizumab, have demonstrated substantial therapeutic efficacy in the treatment of cancer. However, immune-related adverse events, including myasthenia gravis (MG), present significant clinical challenges. This study presents the case of a 75-year-old male patient who developed generalized acetylcholine receptor antibody-positive MG following the first infusion of pembrolizumab for cholangiocarcinoma. The patient’s symptoms rapidly progressed to an impending myasthenic crisis (MGFA Class IVB) within 20 days of pembrolizumab administration. Eculizumab was used as a rescue therapy due to the unavailability of conventional treatments, resulting in rapid and significant symptom relief, with sustained improvement during maintenance therapy. The use of eculizumab as rescue therapy presents a viable treatment option for pembrolizumab-induced MG, owing to its rapid therapeutic effects.